HYPEREMIA: PATHOPHYSIOLOGICAL MECHANISMS, HEMODYNAMIC CHANGES AND CLINICAL SIGNIFICANCE (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Hyperemia is a hemodynamic condition characterized by an increase in blood volume in tissues and organs, which develops under the influence of physiological or pathological factors. The article comprehensively discusses the etiology, pathogenesis, microcirculatory changes and clinical significance of hyperemia.